THE INFLUENCE OF CLAY MINERALS ON HIGHWAY DAMAGE IN THE KLABEN AREA, MARIAT DISTRICT, SORONG DISTRICT, SOUTHWEST PAPUA: PENGARUH MINERAL LEMPUNG TERHADAP KERUSAKAN JALAN RAYA DI DAERAH KLABEN, DISTRIK MARIAT, KABUPATEN SORONG, PAPUA BARAT DAYA - Salomina Opur; Restu Tandirerung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2024)
The proportion of clay minerals in the mudstone that supports road construction also influences damage to the road body. This research aims to determine the content and role of clay minerals in damage to highway construction in the research area. The clay minerals studied came from the claystone of the Klasaman Formation. The clay mineral content in rocks is determined by carrying out X-ray Diffraction (XRD) analysis and petrographic analysis. Of the two (2) samples analyzed, it is known that the illite mineral presentation is very dominant. The dominant proportion of the mineral illite causes road damage, including cracked crocodile skin, holes and sinking.